2017
DOI: 10.1002/masy.201600130
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Surface Free Energy of Poly(lactic acid) During UV‐Grafting with N‐Vinylpyrrolidone

Abstract: The surface free energy (SFE) of polylactic acid (PLA) during grafting with N‐vinylpyrrolidone (NVP) was determined from contact angle measurements using the vOCG, Fowkes’, and Owens‐Wendt methods (Harmonic and Geometric mean approximation equations). A good correlation between the results of the three methods was found. Polymer film was obtained by melt extrusion and grafted with NVP using UV light and benzophenone (BP) as photoinitiator. Comparison of SFE results with those from the literature for pristine P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
(15 reference statements)
2
5
0
Order By: Relevance
“…However, these results remained consistent with the findings from XPS and FTIR that showed the formation of new oxygen-bearing functional groups. The presented contact angles for both the pristine and plasma-treated PLA-T and PLA-MC corresponded to those reported in the literature [36][37][38], as did the observed increase in SFE from 47.9 and 45.8 mJ/m 2 , respectively, to 61.0 and 61.2 mJ/m 2 [30,39]. It must be also noticed that changes induced by plasma are prone to disappear with time [26,37].…”
Section: Contact Angle and Surface Free Energy (Sfe)supporting
confidence: 86%
“…However, these results remained consistent with the findings from XPS and FTIR that showed the formation of new oxygen-bearing functional groups. The presented contact angles for both the pristine and plasma-treated PLA-T and PLA-MC corresponded to those reported in the literature [36][37][38], as did the observed increase in SFE from 47.9 and 45.8 mJ/m 2 , respectively, to 61.0 and 61.2 mJ/m 2 [30,39]. It must be also noticed that changes induced by plasma are prone to disappear with time [26,37].…”
Section: Contact Angle and Surface Free Energy (Sfe)supporting
confidence: 86%
“…Moreover, the increase of Sq could slightly increase the water contact angle of the PLA composite films. The Fowkes model ( Section S1.2, Supporting Information ) was used to calculate the surface free energy, and the results are shown in Figure 4 h [ 37 , 38 ]. The higher surface free energy indicated that the surface could be wetted easily (a small value of contact angle), which was in good agreement with the change of water contact angle.…”
Section: Resultsmentioning
confidence: 99%
“…These parameters could be determined from contact angle (θ) measurements [ 23 ]. Moreover, the water contact angle (θ w ) allows prediction of the hydration properties of materials [ 24 ], which is an important issue during active compound release.…”
Section: Resultsmentioning
confidence: 99%